2011
DOI: 10.1177/0956797611408736
|View full text |Cite
|
Sign up to set email alerts
|

Integration Without Awareness

Abstract: Human conscious awareness is commonly seen as the climax of evolution. However, what function-if any-it serves in human behavior is still debated. One of the leading suggestions is that the cardinal function of conscious awareness is to integrate numerous inputs-including the multitude of features and objects in a complex scene-across different levels of analysis into a unified, coherent, and meaningful perceptual experience. Here we demonstrate, however, that integration of objects with their background scene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 39 publications
4
121
1
Order By: Relevance
“…This finding demonstrates that the meaning of words is indeed extracted and integrated non-consciously. Along the same lines, Mudrik et al (2011) showed that scenes containing incongruent objects (e.g., Michael Jordan holding a watermelon) broke through suppression faster than the same scenes containing congruent objects (e.g., Michael Jordan holding a basketball). The authors stress that dissociating a coherent from an incoherent image requires the integration of an object in its semantic context; a process originally thought to require consciousness (e.g., Edelman and Tononi, 2000).…”
Section: Effects Of Stimulus Contentmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding demonstrates that the meaning of words is indeed extracted and integrated non-consciously. Along the same lines, Mudrik et al (2011) showed that scenes containing incongruent objects (e.g., Michael Jordan holding a watermelon) broke through suppression faster than the same scenes containing congruent objects (e.g., Michael Jordan holding a basketball). The authors stress that dissociating a coherent from an incoherent image requires the integration of an object in its semantic context; a process originally thought to require consciousness (e.g., Edelman and Tononi, 2000).…”
Section: Effects Of Stimulus Contentmentioning
confidence: 83%
“…Consequently, these studies do not attribute their findings to high level processing under continuous flash suppression. Importantly, three out of four b-CFS experiments that led the authors to conclude from their data that the observed difference in suppression durations was caused by semantic or conceptual analysis of the stimuli under CFS, however, did not include such a control condition (i.e., Costello et al, 2009; Mudrik et al, 2011; Sklar et al, 2012). Thus far, the only study that convincingly demonstrates high-level competition in a b-CFS experiment, is that of Yang and Yeh (2011).…”
Section: Discussionmentioning
confidence: 98%
“…4As in for what we noted regarding face processing, much more evidence of semantic processing was obtained using bCFS (Jiang et al, 2007; Costello et al, 2009; Mudrik et al, 2011; Yang and Yeh, 2011; Sklar et al, 2012). …”
mentioning
confidence: 77%
“…A rapidly growing body of literature using b-CFS now suggests that interocular suppression allows for a much greater extent of high-level unconscious processing than previously thought (for a review, see Gayet et al, submitted). For example, b-CFS is sensitive to various features of face stimuli (Jiang et al, 2007; Yang et al, 2007; Zhou et al, 2010; Stein et al, 2011b,c, 2012b, 2014; Chen and Yeh, 2012; Stein and Sterzer, 2012; Stewart et al, 2012; Gobbini et al, 2013a,b), and can even be influenced by semantic stimulus properties (Costello et al, 2009; Mudrik et al, 2011; Sklar et al, 2012). These findings demonstrate that b-CFS is highly sensitive to differences between complex stimuli in their potency to gain access to awareness.…”
Section: Breaking Continuous Flash Suppression (B-cfs)mentioning
confidence: 99%